(untitled) (Clinics, 2005)
PURPOSE: To study the results including long-term follow-up obtained with endovascular treatment of patients with intermittent claudication who did not experience clinical improvement with conservative treatment. METHODS: From January 1992 to January 2002, 62 of 1380 patients (4.5%) with intermittent claudication underwent endovascular treatment and were followed up for up to 120 months (mean 76 months). The variables analyzed were the functioning of the arterial segment undergoing the endovascular procedure, the evolution of the maximum walking distance, and incidence of related morbidity and mortality. RESULTS: Fifty-two patients (84%) experienced no walking limitation after the procedure, and 6 patients (10%) improved but still exhibited some degree of limitation, for a total improved outcome of 94%. The patency rate was 82%. There was no intraoperative mortality. One primary failure and one immediate thrombosis occurred, and both were surgically corrected. Thrombosis of the treated artery occurred in 6 patients 12, 16, 25, 29, 62, and 66 months after the procedure. These patients started to experience intermittent claudication with a walking distance to onset that was similar to their presurgical distance to onset. During follow-up, a mortality rate of 12.9% (8 patients) was observed, 6 due to myocardial infarctions and 2 due cerebral infarction. Three patients underwent coronary bypasses 22, 36, and 55 months after the endovascular surgery, and 2 patients underwent coronary angioplasty after 6 and 26 months. The mean follow up period was 76 months (range 0-120 months). CONCLUSION: This study shows that endovascular treatment of intermittent claudication brought about a lasting regression of the ischemic conditions in a significant number of patients, with excellent patency rates. It was concluded that this is a good alternative for selected patients, with low rates of complications and positive long-term results.